Five‐year clinical outcomes of a polymer‐free sirolimus‐eluting stent versus a permanent polymer paclitaxel‐eluting stent: Final results of the intracoronary stenting and angiographic restenosis – test equivalence between two drug‐eluting stents (ISAR‐TEST) trial1. Issue 1 (4th May 2012) - King, Lamin; Byrne, Robert A.; Mehilli, Julinda; Schömig, Albert; Kastrati, Adnan; Pache, Jurgen
Abstract Background Limited evidence exists regarding the long‐term performance of polymer‐free (PF) drug‐eluting stents (DES) in comparison to permanent polymer DES. This study investigated the 5‐year efficacy and safety of a PF sirolimus‐eluting stent (PF‐SES) versus a permanent polymer paclitaxel‐eluting stent (PES) in the setting of the Intracoronary Stenting and Angiographic Restenosis‐Test Equivalence Between Two Drug‐Eluting Stents (ISAR‐TEST) randomized trial. Methods and Results A total of 450 patients undergoing percutaneous coronary intervention were randomized to receive either PF‐SES (Yukon, Translumina; n = 225) or PES (Taxus, Boston Scientific; n = 225). Clinical follow‐up was performed to 5 years after enrollment. The endpoints were major adverse cardiac events (MACE), target lesion revascularization (TLR), the composite of death or any myocardial infarction (MI) and stent thrombosis (ST). The incidence of MACE at 5 years was 27.3% (57 patients) in the PF‐SES group and 31.7% (65 patients) in the PES group [hazard ratio (HR) = 0.87 [95% confidence interval (95% CI) = 0.61–1.24]; P = 0.40]. The combined incidence of death or MI was 16.6% (34 patients) in the PF‐SES group and 20.0% (39 patients) in the PES group (HR = 0.86 [95% CI = 0.54–1.36]; P = 0.52). The incidence of TLR was 16.5% (34 patients) in the PF‐SES group and 16.4% (33 patients) in the PES group (HR = 1.03 [95% CI = 0.64–1.66]; P = 0.89). ST occurred in 0.5% (one patient) in the PF‐SES group and 1.6% (three patients) in the PES group (HR = 0.33 [95% CI = 0.03–3.14]; P = 0.32). Conclusion Overall there was no significant difference in clinical outcomes between PF‐SES and PES to 5 years. Extended follow‐up supports the durability of efficacy and safety of PF‐SES. © 2012 Wiley Periodicals, Inc.